Soft X-Ray Emission in the Water Window Region with Nitrogen Filling in a Low Energy Plasma Focus - Akel, M.; Lee, S. (Springer US, 2013)
For operation of the plasma focus in nitrogen, a focus pinch compression temperature range of 74–173 eV (0.86 × 106–2 × 106 K) is found to be suitable for good yield of nitrogen soft X-rays in the water window region. Using this temperature window, numerical experiments using five phase Lee model have been investigated on UNU/ICTP PFF and APF plasma focus devices with nitrogen filling gas. The Lee model was applied to characterize and optimize these two plasma focus devices. The optimum nitrogen soft X-ray yield was found to be Ysxr = 2.73 J, with the corresponding efficiency of 0.13 % for UNU/ICTP PFF device, while for APF device it was Ysxr = 4.84 J, with the corresponding efficiency of 0.19 % without changing the capacitor bank, merely by changing the electrode configuration and operating pressure. The Lee model code was also used to run numerical experiments for optimizing soft X-ray yield with reducing L0, varying z0 and ‘a’. From these numerical experiments we expect to increase the nitrogen soft X-ray yield of low energy plasma focus devices to maximum value of near 8 J, with the corresponding efficiency of 0.4 %, at an achievable L0 = 10 nH.